CD4hiCD8low Double-Positive T Cells Are Associated with Graft Rejection in a Nonhuman Primate Model of Islet Transplantation - Yun Jung Choi; Hi-Jung Park; Hye Jin Park; Kyeong Cheon Jung; Jae-Il Lee (Journal of Immunology Research)
Peripheral CD4/CD8 double-positive (DP) T cells are associated with autoimmune disorders, cancer, and viral infection. However, the relationship between organ transplantation and DP T cells is unclear. Here, we examined the functional characteristics of peripheral DP T cells and analyzed their significance with respect to islet graft rejection in a nonhuman primate model of islet transplantation. DP T cells were functionally equivalent to conventional CD4 and CD8 T cells in terms of helper and cytotoxic activity, respectively. DP T cells expressed high levels of CXCR5 and PD-1 and secreted IFN-γ, IL-4, and IL-21 in amounts equivalent to those secreted by CD4 or CD8 T cells; also, they produced large amounts of granzyme B and perforin. In addition, under steady-state conditions, DP T cells expressed eomesodermin (Eomes) and promyelocytic leukemia zinc finger (PLZF) proteins, both of which act as transcription factors in innate/memory-like T cells. The number of peripheral DP T cells in the islet transplantation model was high in the group that experienced graft rejection; this was not the case in the long-term survival group. Interestingly, numbers of effector memory T cells (TEM) within the DP T cell population increased significantly during islet graft rejection, as did those of TEM within the cytotoxic CD8 T cells. Furthermore, the most conspicuous of which was the increase of CD4hiCD8low T cell subpopulation at that point. Taken together, the data suggest that peripheral DP T cells showing an innate/memory-like phenotype have both helper and cytotoxic activity in vitro and that they may act as a novel biomarker for graft rejection after islet transplantation.